Case Report: Response to crizotinib treatment in a patient with advanced non-small cell lung cancer with LDLR-ROS1 fusion - Shu, Yun; Wang, Zhouyu; Shang, Hongjuan; Le, Wei; Lei, Yan; Huang, Longzhang; Tao, Liming; Chen, Jun; Li, Jing (Frontiers in Oncology, 2023)
C-ros oncogene 1 (ROS1) fusion is a pathogenic driver gene in non-small cell lung cancer (NSCLC). Currently, clinical guidelines from the National Comprehensive Cancer Network (NCCN) have recommended molecular pathologic tests for patients with NSCLC, including the detection of the ROS1 gene. Crizotinib is a small molecule tyrosine kinase inhibitor of anaplastic lymphoma kinase (ALK), ROS1, and mesenchymal-epithelial transition (MET). In recent years, the efficacy of crizotinib in NSCLC patients with ROS1 fusion has been reported. Here, a 77-year-old woman was diagnosed with stage IVA lung adenocarcinoma harboring a novel low-density lipoprotein receptor (LDLR)-ROS1 fusion variant. This novel LDLR-ROS1 fusion was identified by targeted DNA next-generation sequencing (NGS) panel and then verified by RNA fusion panel based on amplicon sequencing. This patient benefited from subsequent crizotinib therapy and achieved progression-free survival of 15 months without significant toxic symptoms. Our case report recommended a promising targeted therapeutic option for patients with metastatic NSCLC with LDLR-ROS1 fusion and highlighted the importance of genetic testing for accurate treatment.